DAYA HAMBAT INFUSA DAUN BAYAM UNGU (Alternanthera brasiliana Kuntze.) TERHADAP PERTUMBUHAN Escherichia coli - Kayani, Wisma; Fifendy, Mades; Rizki, Rizki (Pendidikan Biologi, 2013)
ABSTRACT Bayam ungu (Alternanthera brasiliana Kuntze.) efficacious for treating various diseases . Parts  used  are the leaves.  Spinach  purple   has a chemicals  such  as  tannins,  saponins,  and flavonoids. Escherichia coli is a bacteria found in that stout opportunist in human colon as normal flora. Escherichia coli suspected as a cause of diarrhea that sometimes arise in humans and animals . Research has been conducted in order to determine the inhibitory infusa purple leaf spinach (Alternanthera brasiliana Kuntze.) on the growth of Escherichia coli. This research was conducted at the Laboratory of Basic Biology Education Program STKIP PGRI West Sumatera in January 2013 , using a completely randomized design with 6 treatments and 4 replications with each infusion concentrations were 10 % , 20 % , 30 % , 40 % , 50 %. Analysis of the data showed that treatment with each test level α f 5 % and followed by BNT test. The results showed that infusion violet leaf spinach (Alternanthera brasiliana Kuntze.) could inhibit the growth of Escherichia coli.